Enthalpy-entropy compensations in drug-DNA binding studies. - Breslauer, K J (1987)
We present a comparative study of calorimetrically derived thermodynamic profiles for the binding of a series of drugs with selected DNA host duplexes. We use these data to demonstrate that comparisons between complete thermodynamic profiles (delta G zero, delta H zero, delta S zero, delta Cp) are required before drug binding can be used as a probe of DNA conformation, since enthalpy-entropy compensations can cause two drug-DNA binding events to exhibit similar binding free energies (delta G zero) despite being driven by entirely different thermodynamic forces (delta H zero, delta S zero). In this work, we employ a combination of spectroscopic and calorimetric techniques to characterize thermodynamically the DNA binding of netropsin and distamycin (two minor groove-directed ligands), ethidium (an intercalator), and daunomycin (a combined intercalator/groove binder). Our free energy data (delta G zero) show that each drug exhibits similar binding affinities at 25 degrees C for the alternating copolymer duplex poly[d(A-T)].poly[d(A-T)] and for the homopolymer duplex poly(dA).poly(dT). However, our calorimetric measurements reveal that the nature of the thermodynamic forces (delta H zero, delta S zero) that drive drug binding to these two host duplexes at 25 degrees C are entirely different, despite similar binding free energies (delta G zero) and similar salt dependencies (lnK/ln[Na+]). Specifically, the 25 degrees C binding of all four drugs to the alternating copolymer poly[d(A-T)].poly[d(A-T)] is overwhelmingly enthalpy driven, whereas the corresponding binding of each drug to the homopolymer duplex poly(dA).poly(dT) is overwhelmingly entropy driven. Thus, the similar binding free energies (delta G zero) we measure for complexation of each drug with poly[d(A-T)].poly[d(A-T)] and poly(dA).poly(dT) result from compensating changes in the enthalpy and entropy terms. Comparison with the thermodynamic profiles for the complexation of these drug molecules to other DNA host duplexes at 25 degrees C reveals that the binding of each is strongly enthalpy driven, except when the poly(dA).poly(dT) homopolymer serves as the host duplex. This comparison allows us to conclude that poly[d(A-T)].poly[d(A-T)] behaves thermodynamically as the more "normal" host duplex toward drug binding, whereas the entropy-driven binding to the poly(dA).poly(dT) duplex represents "aberrant" behavior. Furthermore, since each of the four drugs exhibits different modes of DNA binding, we conclude that the observed entropy-driven behavior for binding to poly(dA).poly(dT) reflects an intrinsic property of the homopolymer duplex that is perturbed in a common manner upon ligation rather than a common property of all four binding ligands. To rationalize the large positive entropy changes that drive drug complexation with poly(dA).poly(dT) duplex, we propose a model that emphasizes binding-induced perturbations of the more highly hydrated, altered B conformation of the homopolymer. Our results suggest that an aberrant thermodynamic binding profile may reflect an unusual DNA conformation in the host duplex. However, before such a conclusion can be reached, complete thermodynamic binding profiles must be examined, since enthalpy-entropy compensations can cause two binding events to exhibit similar binding constants even when they are driven by very different thermodynamic forces.